Preceptors' and nursing students' experiences of using peer learning in primary healthcare settings: a qualitative study - Taghrid Jassim; Elisabeth Carlson; Mariette Bengtsson (BMC, 2022)
Abstract Background Due to the need for students to integrate theory with practice, current research seeks the best learning and teaching models in primary healthcare settings. The aim of this study was to explore preceptors' and nursing students' experiences of using peer learning during clinical practice in primary health care. Methods A qualitative research approach was used based on semi-structured interviews with seven preceptors and ten nursing students. The interviews were transcribed and analyzed by using content analysis based on an inductive reasoning. Results Preceptors and students perceived peer learning as an educational model to be beneficial for learning in primary care settings. They found the model to be stimulating, challenging, and leading to development of professional identity and nursing skills. All informants were positive towards the peer learning experience, with students reporting they were seen as individuals, despite working in pairs. However, the physical environment was demanding with regards to telephone counseling issues, limited opportunities for using computers, and the use of small examination rooms. Conclusion This study shows that, despite the complex learning environment, peer learning as an educational model appears to work well in a primary healthcare setting. However, much improvement is needed to facilitate the students' learning process. Consequently, conditions for clinical practice and learning beneficial to both students and preceptors should be prioritized by management.